Dawn of a New Normal: Resident and Faculty Attitudes in Adopting Virtual Conferences and Education. Issue 10 (October 2022) - Frank, Madelyn; Stopenski, Stephen; Yamamoto, Maki; Nahmias, Jeffry; Nguyen, Ninh T.; Smith, Brian R.; Keshava, Hari B.
Background: The COVID-19 pandemic has dramatically changed education in medical residencies with the need to transition to a virtual format. The objective of this study is to assess the adoption of a virtual format for grand rounds, M&M, and education of the surgical department. Method: A 25 question online survey was developed using Qualtrics and distributed to faculty and resident physicians in the Department of Surgery from March to April 2021. Results: Fifty four out of 79 potential respondents (68%) completed the survey. Twenty-seven out of 54 (50%) respondents stated they were more likely to be participating in another activity most of the time or always. During to in-person conferences, 20/54 (37%) of participants reported being more distracted by other activities. Forty-two out of 54 (78%) participants strongly agree that virtual conferences are more flexible with their schedule and saves them travel time. All of the faculty want conferences to continue virtually (with or without an in-person component) citing virtual conferences are more flexible with their schedule and saves travel time. However, 4/26 (15%) of residents responded not wanting to continue virtual education citing work distractions and not truly having protected time. Conclusion: As the Coronavirus 2019 (COVID-19) pandemic is continuing with new variants, the virtual education and conference format is necessary. There is overwhelming support from both residents and faculty in favor of the virtual conference format due to flexibility, ease, and convenience. However, care must be taken to make sure that resident education time is truly protected.